A szülői felügyelet szabályozása a magyar jogfejlődésben - Gothárdi, Enikő (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2021)
The purpose of this paper is to briefly present the development of legal regulation and judicial practice of parental responsibility in Hungary, from the age of the so called traditional law before 1848 until the entry into force of the new Hungarian Civil Code in 2014, including some outlook to the concurrent progress in other European countries. The study shows how paternal power turned to parental power in the 19th and then parental responsibility in the 20th century, and particularly examines that in case of divorce or break-up of the parents, which parent, on what grounds and in what type of procedure was empowered to exercise – elements of – parental responsibility.